2014
DOI: 10.1103/physreve.89.032713
|View full text |Cite
|
Sign up to set email alerts
|

Role of functionality in two-component signal transduction: A stochastic study

Abstract: We present a stochastic formalism for signal transduction processes in a bacterial two-component system. Using elementary mass action kinetics, the proposed model takes care of signal transduction in terms of a phosphotransfer mechanism between the cognate partners of a two-component system, viz., the sensor kinase and the response regulator. Based on the difference in functionality of the sensor kinase, the noisy phosphotransfer mechanism has been studied for monofunctional and bifunctional two-component syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This could be advantageous for the organism when the concentrations of the components varies from cell to cell. Thus all the cells would respond in the same way for a given input, and there would be no heterogeneity among the cells (19,20). Using a model of phosphotransfer kinetics in a bifunctional two-component system, Batchelor and Goulian (8) and Shinar et al (9) showed that the output of a TCS is directly proportional to the input signal.…”
Section: Discussionmentioning
confidence: 99%
“…This could be advantageous for the organism when the concentrations of the components varies from cell to cell. Thus all the cells would respond in the same way for a given input, and there would be no heterogeneity among the cells (19,20). Using a model of phosphotransfer kinetics in a bifunctional two-component system, Batchelor and Goulian (8) and Shinar et al (9) showed that the output of a TCS is directly proportional to the input signal.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the concentration of R p in a bifunctional system is robust to variations in the concentration of the histidine kinase and the response regulator itself, when the response regulator is present in large excess compared to the kinase [27,28]. This property is not present in monofunctional systems [26].…”
Section: A Bacterial Two-component Systemmentioning
confidence: 99%
“…The extended model has the same variables and parameters as the Cph8-OmpR model except the transition rates of histidine kinase. Here we focused on the state transition itself as a source of noise with saturating input [24]. Note that the ratio of transition rates v act to v ina (from inactive to active kinase state and vice versa) determines the active fraction of histidine kinase.…”
Section: Output Noise Attenuation In Fast Protein Activity Transitionmentioning
confidence: 99%
“…Although any transition of a component in a biological system inevitably generates noise with a frequency equal to that of the transition [24], this noise can be cancelled when such a component is in an upstream position in the a cascade and has a high-frequency transition. Cascade systems have a low-pass filter property through signal transduction [23,36] and can reduce the high-frequency noise generated in the upstream process.…”
Section: Output Noise Attenuation In Fast Protein Activity Transitionmentioning
confidence: 99%